2017
DOI: 10.1186/s12891-017-1813-9
|View full text |Cite|
|
Sign up to set email alerts
|

A new multiple trauma model of the mouse

Abstract: BackgroundBlunt trauma is the most frequent mechanism of injury in multiple trauma, commonly resulting from road traffic collisions or falls. Two of the most frequent injuries in patients with multiple trauma are chest trauma and extremity fracture. Several trauma mouse models combine chest trauma and head injury, but no trauma mouse model to date includes the combination of long bone fractures and chest trauma. Outcome is essentially determined by the combination of these injuries. In this study, we attempted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…In our previous findings, a CT scan of TxT group has shown intrathoracic bleeding and hemopneumothorax without rib fractures, while the histological analyses reflected hemothorax and lung contusion in this model 12 . Here, cardiac rupture, pericardial laceration, laceration to a coronary artery followed by hemothorax or complex lung contusion caused the mortality after chest trauma.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In our previous findings, a CT scan of TxT group has shown intrathoracic bleeding and hemopneumothorax without rib fractures, while the histological analyses reflected hemothorax and lung contusion in this model 12 . Here, cardiac rupture, pericardial laceration, laceration to a coronary artery followed by hemothorax or complex lung contusion caused the mortality after chest trauma.…”
Section: Discussionsupporting
confidence: 56%
“…Among several available femur fracture models, here, external fixation model was chosen. Fracture can be fixed with intramedullary Kirschner wires or syringe needles as well, imitating human intramedullary nailing without applying locking screws 12,58 . However, single intramedullary Kirschner wires or syringe cannot provide rotational and axial stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common in vivo trauma models combine mainly two insults to better imitate the human conditions 9,[21][22][23][24][25][26] . However, considering the definition of polytrauma according to the ISS or the new Berlin Group allocation and experimental model.…”
mentioning
confidence: 99%
“…A previous study reported the physiological and immunological characterization of a long-term model of blunt chest trauma in mice using a blast wave generator (3). Another approach for inducing blunt chest trauma is dropping a weight from a defined height, which has been used in multiple rat and murine trauma models (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%